Micropore Structure Characteristics and Recoverability Evaluation of Typical Shale Oil Reservoirs - Lanlan Yao; Zhengming Yang; Haibo Li; Meng Du; Tiyao Zhou; Yapu Zhang; Qianhui Huang; Xinliang Chen; Ning Wang (Lithosphere, 2023)
In view of the weak research on the availability of typical shale oil reservoirs from the perspective of development, this study introduced a two-dimensional nuclear magnetic resonance (NMR) evaluation method on the basis of the previous one-dimensional NMR combined with centrifugal physical simulation experiments. Not only the production characteristics of typical shale oil reservoirs were studied but also the microscopic production laws of different occurrence states were studied. The results show that the pore distribution of Jilin shale is more concentrated than that of Qinghai shale. The oil of the two blocks mainly occurs in 0.01–10 ms pores, and the occurrence ratio of Jilin shale in the pores is higher, which is more than 90%. The oil production of the two blocks is mainly dominated by 0.01–10 ms pores, and the utilization efficiency contribution of these pores in Jilin shale is higher, accounting for about 80%. The utilization efficiency (UE) increases logarithmically with centrifugal force, and the growth rate of Jilin shale is greater than that of Qinghai shale. The proportion of free oil in Jilin block is less than that in Qinghai block. The shale oil in the two blocks is both at 15% final UE, and the UE of free oil in Jilin shale is about 9% and that of Qinghai shale is about 12%. The recoverability of Jilin shale is lower than that of Qinghai shale.